A Similar Place: Resistance and Existence in 21st Century Black and Native Women's Memoirs. (February 2017) - Warburton, Theresa
In 2014, Nishnaabeg scholar Leanne Simpson connected #BlackLivesMatter and #MMIWG2S by highlighting their existence in "a similar place." Here, I interpret this as a space of shared emotion and geography, emphasizing the land on which anti-Black and colonial violences occur. I argue that this provides a methodology for the study of multiethnic literature in a way that reckons with the interrelatedness of settler colonialism and anti-Black racism without conflating them under the auspices of "multiculturalism." I read memoirs by Deborah Miranda and Jesmyn Ward to explore how they articulate the relationship between personal and spatial history.